Dietary stearic acid regulates mitochondria in vivo in humans - Senyilmaz-Tiebe, Deniz; Pfaff, Daniel; Virtue, Sam; Schwarz, Kathrin V.; Fleming, Thomas; Altamura, Sandro; Muckenthaler, Martina; Okun, Jürgen G.; Vidal-Puig, Antonio; Nawroth, Peter Paul; Teleman, Aurelio A. (Nature Communications, 2018)
Since modern foods are unnaturally enriched in single metabolites, it is important to understand which metabolites are sensed by the human body and which are not. We previously showed that the fatty acid stearic acid (C18:0) signals via a dedicated pathway to regulate mitofusin activity and thereby mitochondrial morphology and function in cell culture. Whether this pathway is poised to sense changes in dietary intake of C18:0 in humans is not known. We show here that C18:0 ingestion rapidly and robustly causes mitochondrial fusion in people within 3 h after ingestion. C18:0 intake also causes a drop in circulating long-chain acylcarnitines, suggesting increased fatty acid beta-oxidation in vivo. This work thereby identifies C18:0 as a dietary metabolite that is sensed by our bodies to control our mitochondria. This could explain part of the epidemiological differences between C16:0 and C18:0, whereby C16:0 increases cardiovascular and cancer risk whereas C18:0 decreases both.
Gesehen am 02.10.2019